Correction: Management of Cardiovascular Disease Patients With Confirmed or Suspected COVID-19 in Limited Resource Settings. Issue 1 (7th August 2020) - Prabhakaran, Dorairaj; Perel, Pablo; Roy, Ambuj; Singh, Kavita; Raspail, Lana; Faria-Neto, José Rocha; Gidding, Samuel S.; Ojji, Dike; Hakim, Ferdous; Newby, L. Kristin; Stępińska, Janina; Lam, Carolyn S. P.; et al.
This article details a correction to the article: Prabhakaran D, Perel P, Roy A, Singh K, Raspail L, Faria-Neto JR, et al. Management of Cardiovascular Disease Patients With Confirmed or Suspected COVID-19 in Limited Resource Settings. Global Heart . 2020; 15(1): 44. DOI:http://doi.org/10.5334/gh.823